Modern Approach To The Diagnosis And Treatment Of Necrotising Enterocolitis In Neonates (Eurasian Medical Research Periodical, 2024)
one of the most severe diseases in newborns - necrotizing enterocolitis - is analysed from the modern point of view. Causes and risk factors of the disease development are considered. The peculiarities of pathogenesis and microbiological status of newborns are shown. The clinical picture of necrotising enterocolitis is covered in detail, clinical stages of the disease, on which its classification is based, are analysed. It is shown that the choice of therapeutic tactics depends on the severity of the child's condition and the stage of the process. At I and II stages of the disease conservative therapy is carried out, at III stage both conservative and operative treatment is possible, at IV stage emergency surgery is indicated. The operation of choice is the technique of decompressive intestinal stomas, which helps to preserve the length of the intestine as much as possible and reduces the risk of postoperative complications.